IMPLEMENTATION OF BIM 5D IN THE IMPLEMENTATION PLAN OF THE TRANS SUMATRA – JAMBI TOLL ROAD WITH CIVIL 3D AND NAVISWORK - Ariany Frederika; I Gusti Agung Adnyana Putera; I Nyoman Aditya Prabawa (Universitas Udayana, 2025)
Significant contributions to technological advancement are helpful in various aspects of work. In Circular Letter 11/SE/Db/2021, it is emphasized that the use of Building Information Modelling (BIM) must be applied in the planning stage of highway construction. 3D and 5D modeling can be done using Autodesk Civil 3D, while 4D modeling can be facilitated through Autodesk Navisworks. This study takes the Trans Sumatra Jambi Toll Road Project as an object of study with the aim of modeling toll roads using BIM-based Autodesk Civil 3D, analyzing the estimated costs from the modeling results, and visualizing the progress plan of mainroad work at a certain time through Autodesk Navisworks. Secondary data includes DED, BoQ and HSP. Modeling was performed on Autodesk Civil 3D including modeling of excavations and embankments as well as road pavement and drainage structures, Clash detection using Autodesk Naviswork, volume of work integrated using Microsoft Project and time simulation using Autodesk Naviswork. The results of the study show that from the modeling that has been carried out, the estimated cost of mainroad work has a deviation of -3.24% from the BoQ document. Comparison of data shows that the estimated volume and cost generated using the Autodesk Civil 3D BIM method is smaller than the conventional method. Simulated mainroad work progress display using Autodesk Naviswork software shows construction simulations, time progress tracking, and cost estimation in an integrated and informative manner to support project decision-making.